2022
DOI: 10.3390/ijerph191710524
|View full text |Cite
|
Sign up to set email alerts
|

Social and Family Challenges of Having a Child Diagnosed with Phelan-McDermid Syndrome: A Qualitative Study of Parents’ Experiences

Abstract: (1) Background: Phelan-McDermid Syndrome (PMS) in children causes significant challenges affecting social and family relationships. The purpose of this study was to explore the experience of parents with children diagnosed with PMS regarding interactions with their social environment; (2) Methods: A qualitative descriptive study was conducted. Participants were recruited using non-probabilistic purposeful sampling. In total, 32 parents of children with PMS were included. In-depth interviews and researchers’ fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 36 publications
1
15
0
9
Order By: Relevance
“…Similar results were recorded in parents of children with Phelan–McDermid syndrome, 34 who perceived that the emergency department professionals lacked experience and knowledge in the management of DEEs and showed a lack of sensitivity towards their children. On occasions, parents described how health care professionals did not believe the symptoms they were told, and this caused them not to reveal the Phelan–McDermid diagnosis to receive better care or avoid delaying their child's care in the emergency room, changing the diagnosis to the more familiar autism spectrum disorder 34 . Previous studies 35,36 revealed that lack of knowledge about rare diseases leads to a decrease in therapeutic involvement with children, reluctance of parents to go to the doctor, and mistrust towards health care specialists.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Similar results were recorded in parents of children with Phelan–McDermid syndrome, 34 who perceived that the emergency department professionals lacked experience and knowledge in the management of DEEs and showed a lack of sensitivity towards their children. On occasions, parents described how health care professionals did not believe the symptoms they were told, and this caused them not to reveal the Phelan–McDermid diagnosis to receive better care or avoid delaying their child's care in the emergency room, changing the diagnosis to the more familiar autism spectrum disorder 34 . Previous studies 35,36 revealed that lack of knowledge about rare diseases leads to a decrease in therapeutic involvement with children, reluctance of parents to go to the doctor, and mistrust towards health care specialists.…”
Section: Discussionsupporting
confidence: 73%
“…31,34 Not knowing the disease, lack of a clear treatment, not recognizing or validating the family's experience, or not listening to them causes loss of confidence in the ability and empathy of the health care professional. 16,31,34 In contrast, the relationship and trust are strengthened when the professional admits lack of knowledge and provides alternatives, maintains close and continuous contact, and shows interest in the evolution of the disease and the patient's situation. 31,34 Our participants had difficulties when going to the emergency department.…”
Section: Therapeutic Relationship and Medical Carementioning
confidence: 99%
See 1 more Smart Citation
“…31,34 El desconocimiento de la enfermedad, la ausencia de un tratamiento claro, no reconocer o validar la experiencia de la familia, o no escucharles o empatizar, provoca pérdida de confianza en la capacidad del profesional sanitario. 16,31,34 Por el contrario, la relación y la confianza se fortalecen cuando el profesional admite la falta de conocimiento y ofrece alternativas, mantiene un contacto estrecho y continuo, y muestra interés por la evolución de la enfermedad y la situación del paciente. 31,34 Nuestros participantes presentaron dificultades para acudir al servicio de urgencias.…”
Section: Relación Terapéutica Y Atención Médicaunclassified
“…En ocasiones, los progenitores describieron cómo los profesionales sanitarios no se creían los síntomas que les contaban, y esto provocaba que los progenitores no revelasen el diagnóstico de Phelan-McDermid para recibir una mejor atención o evitar retrasar la atención de su hijo en urgencias, cambiando el diagnóstico por el de trastorno del espectro autista, que es más conocido. 34 Estudios previos 35,36 muestran que el desconocimiento de las enfermedades raras conlleva una disminución de la implicación terapéutica con los niños, reticencia de los progenitores a acudir al médico y desconfianza hacia los especialistas sanitarios. Los autores del presente estudio consideran que el servicio de urgencias, al estar orientado a la resolución de problemas agudos, no permite una relación continuada y prolongada en el tiempo, que permita construir una relación de confianza entre los profesionales y los progenitores de niños con EED.…”
Section: Relación Terapéutica Y Atención Médicaunclassified